(untitled) (Journal of Pathology of Nepal, 2015)
Background: Oral cancer is the sixth most common cancer in the world. P53 mutations are associated with the development of oral squamous cell carcinomas. This study is to determine the presence of p53 oncogene expression in cases of oral malignant, premalignant and benign lesions and to show association of p53 oncogene and lymph node enlargement in malignant lesion. Materials and Methods: Four to five micron-thick sections of formalin fixed, paraffin embedded biopsy material from various intra-oral sites of 50 patients were collected, in the series of 50 cases, 35 oral squamous cell carcinoma, 10 dysplastic lesions and 05 hyperplastic lesions were assessed for p53 expression. The tissue sections were immunohistochemically analyzed for the expression of p53 gene. Results: Out of 50; 22/35 (63%) cases of squamous cell carcinoma, 02/10 (20%) cases of dysplasia (20%), were positive for p53. Five hyperplastic lesions were negative for p53. The P53 protein was not identified in benign lesion. Conclusion: Results indicate that p53 over-expression is seen in oral squamous cell carcinomas. It is a significant marker of carcinogenesis and can be considered as an important marker for clinical evaluation, diagnosis as well as prognosis of disease. Journal of Pathology of Nepal (2015) Vol. 5, 747-751